Imaginarios Sociales y Sustentabilidad - Leff, Enrique (Cultura y Representaciones Sociales, 2010)
This paper is intended to open a sociological inquiry on a crucial problem for the future of humankind: its capacity to respond to the global ecological risk. Starting with a critical overview on the possibilities of a “reflexive modernity” based on science and expert knowledge to slow down, stop and revert the current trends of climate change towards the planet’s entropic death, an inquiry is opened on the social imagery of sustainability embodied in traditional peoples, on their capacity to respond from their local cultural identities, mobilizing new social actors and leading to an environmental democracy from the ecological and cultural conditions instituted in the social imagery and the life worlds of the people that inhabit the living planet.